Exploration and Existence of Local Wisdom as a Marketing Strategy for Sustainable Tourism Development in Banyuwangi - Wilujeng, Ita Prihatining; Zutiasari, Ika; Dhewi, Titis Shinta; Sungkar, Alifia Ratna (Dinasti International Journal of Management Science, 2024)
The tourism sector is one of the supports for the Indonesian economy as well as a major foreign exchange contributor to the country. However, the Covid-19 pandemic in 2020 caused the contribution of tourism to GDP to fall by 56%, namely to only 2.2% of the total economy. According to one online travel service platform in Indonesia, the cities of Bandung, Yogyakarta and Bali are areas that are frequently visited by tourists in Indonesia for domestic and foreign tourists. However, there is one area in East Java which is currently famous for its tourist destination, namely Banyuwangi Regency. Banyuwangi Regency is an area that has very broad tourism potential. However, unfortunately the number of tourists which experienced a decline until the Covid-19 period was over has not yet recovered to the number of visits before the pandemic. Several efforts have been made by Banyuwangi tourism managers in order to increase visits by local and foreign tourists. Several strategies implemented are still not able to increase the number of tourist arrivals in Banyuwangi. This research will focus on conducting exploration and existence as a marketing effort, especially on social media to provide a sustainable tourism impact in Banyuwangi district. A qualitative approach was taken to tourism visitors, tourism business people and tourism managers in Banyuwangi over the past year. Promotion via social media has been proven to be able to provide effective results in attracting tourist visits. Online promotion and maintenance of offline tourism facilities and infrastructure must be able to be carried out to produce sustainable and attractive tourism in the future. It is hoped that this research will be able to provide benefits in sustainable tourism development for the development of tourist cities, especially regarding the tourism sector in Banyuwangi.